China between empires the Northern and Southern dynasties - Lewis, Mark Edward 1954- (History of Imperial China, 2009)
The geography of the northern and southern dynasties -- The rise of the great families -- Military dynasticism in the northern and southern dynasties -- Cities in the northern and southern dynasties -- Rural society in the northern and southern dynasties -- China and the outside world in the northern and southern dynasties -- Kinship in the northern and southern dynasties -- Institutional religions in the northern and southern dynasties -- The literary field of the northern and southern dynasties